We interrupt this broadcast : the events that stopped our lives-- : from the Hindenburg explosion to the death of John F. Kennedy Jr. - Garner, Joe (Sourcebooks, 2000)
Recounts the details of forty-one significant events of the twentieth century, each with from-the-scene photographs; and features two compact discs that contain over two hours of audio from the events as they were broadcast live.